Performance-impact limited area fill synthesis - Chen, Yu; Gupta, Puneet; Kahng, Andrew B. (2003 40th Annual Conference Design Automation, 2003)
Chemical-mechanical planarization (CMP) and other manufacturing steps in very deep-submicron VLSI have varying effects on device and interconnect features, depending on the local layout density. To improve manufacturability and performance predictability, area fill features are inserted into the layout to improve uniformity with respect to density criteria. However, the performance impact of area fill insertion is not considered by any fill method in the literature. In this paper, we first review and develop estimates for capacitance and timing overhead of area fill insertions. We then give the first formulations of the Performance Impact Limited Fill (PIL-Fill) problem with the objective of either minimizing total delay impact (MDFC) or maximizing the minimum slack of all nets (MSFC), subject to inserting a given prescribed amount of fill. For the MDFC PIL-Fill problem, we describe three practical solution approaches based on Integer Linear Programming (ILP-I and ILP-II) and the Greedy method. For the MSFC PIL-Fill problem, we describe an iterated greedy method that integrates call to an industry static timing analysis tool. We test our methods on layout testcases obtained from industry. Compared with the normal fill method [3], our ILP-II method for MDFC PIL-Fill problem achieves between 25-% and 90% reduction in terms of total weighted edge delay (roughly, a measure of sum of node slacks) impact while maintaining identical quality of the layout density control; and our iterated greedy method for MSFC PIL-Fill problem also shows significant advantage with respect to the minimum slack of nets on post-fill layout.